Automatic approach/avoidance tendencies towards food and the course of anorexia nervosa. (1st August 2015) - Neimeijer, Renate A.M.; de Jong, Peter J.; Roefs, Anne
Highlights: We used an Affective Simon Task to measure approach bias towards food in Anorexia. Automatic Approach tendencies (AAT) towards food increased after one year follow up. Change in AAT was not associated with change in eating disorder symptoms. AAT were not predictive for one year follow up. So far, no reason to add a treatment that directly targets (low) AAT in Anorexia. Abstract: Objective: The aim of the present study was to investigate the role of automatic approach/avoidance tendencies for food in Anorexia Nervosa (AN). We used a longitudinal approach and tested whether a reduction in eating disorder symptoms is associated with enhanced approach tendencies towards food and whether approach tendencies towards food at baseline are predictive for treatment outcome after one year follow up. Method: The Affective Simon Task-manikin version (AST-manikin) was administered to measure automatic approach/avoidance tendencies towards high-caloric and low-caloric food in young AN patients. Percentage underweight and eating disorder symptoms as indexed by the EDE-Q were determined both during baseline and at one year follow up. Results: At baseline anorexia patients showed an approach tendency for low caloric food, but not for high caloric food, whereas at 1 year follow up, they have an approach tendency for both high and low caloric food. Change in approach bias was neither associated with change in underweight nor with change in eating disorder symptoms. Strength of approach/avoidance tendencies was not predictive for percentage underweight. Discussion: Although approach tendencies increased after one year, approach tendencies were neither associated with concurrent change in eating disorder symptoms nor predictive for treatment success as indexed by EDE-Q. This implicates that, so far, there is no reason to add a method designed to directly target approach/avoidance tendencies to the conventional approach to treat patients with a method designed to influence the more deliberate processes in AN.